ECONOMIC CONSIDERATIONS AS A FACET OF SUBSTANTIVE UNFAIRNESS OF CONSUMER CONTRACT TERMS IN THE PRACTICE OF POLISH COURTS - Sitnik, Piotr (Review of European and Comparative Law, 2018)
It is trite law and a common cliché reiterated in the judgments of the Court of Justice of the European Union that the economic situation of a consumer subjected to a purportedly unfair consumer contract clause is generally impertinent. This general tenet of the European regulation of unfair terms in consumer contracts is borne out particularly by Article 4(2) of Council Directive 93/13/EEC of 5 April 1993 on unfair terms in consumer contracts, under which assessment of the unfair nature of a term shall not encompass an inquiry into the adequacy of the price and remuneration, on the one hand, as against the services or goods supplies in exchange, on the other, in so far as these terms are in plain intelligible language. Despite this seemingly bold orientation towards the formal side of the unfairness assessment, efforts have been made to inject into the judicial exercise of discretion a degree of consideration of the economic standing and interests of both the consumer and the trader involved in the particular dispute at hand. This has been done primarily by reference to the “significant imbalance” requirement pursuant to Article 3(1) of the Directive. The paper reviews an extensive crosssection of judgments handed down in Polish courts based upon the Polish transposition of the Unfair Terms Directive to show that the courts have on numerous occasions ventured outside the boundaries delineated by traditional legal analysis (even beyond the flexible bounds of purposive interpretation) to scrutinize the size and gravity of the economic burden the term under scrutiny is liable to impose upon the consumer relative to its economic strength on the market.